Bond behaviour between CFRP laminates and steel members under different loading rates. (15th July 2016) - Al-Mosawe, Alaa; Al-Mahaidi, Riadh; Zhao, Xiao-Ling
Abstract: Carbon fibre reinforced polymers are widely used to strengthen steel structural elements. These structural elements are normally subjected to static, dynamic and fatigue loadings during their life-time. A number of studies have focused on the characteristics of CFRP sheets bonded to steel members under static, dynamic and fatigue loadings. However, there is a gap in understanding the bonding behaviour between CFRP laminates and steel members under impact loading. This paper shows the effect of different load rates from quasi-static to 300 × 10 3 mm/min on this bond. Two types of CFRP laminate, CFK 150/2000 and CFK 200/2000, were used to strengthen steel joints using Araldite 420 epoxy. The results show a significant bond strength enhancement under impact loading, whereas the high loading rates have little influence on the effective bond length.